Coded aperture and coded exposure photography : an investigation into applications and methods - Wilson, Martin (Department of Electrical Engineering, 2015)
This dissertation presents an introduction to the field of computational photography, and provides a survey of recent research. Specific attention is given to coded aperture and coded exposure theory and methods, as these form the basis for the experiments performed.